Nature as a value in education for sustainable development - Ciążela, Helena; Tuszyńska, Ligia (Studia Ecologiae et Bioethicae, 2017)
The values related to sustainable development are rooted in fundamental threats which are connected with a human being. The imbalance of development of modern civilization entails a threat to humanity. Concern for the environment which is not taking into account the aspirations and social strivings may become a source of conflicts and tensions that could destabilize the political situation. The article draws attention to the relationship of man with nature from an early age. The formation of values in relation to the surrounding nature and the nearest child’s environment may contribute to sustainable development.